Feeding Practices in Small Holder Production System by Dairy Farmers of Meerut District, Uttar Pradesh (Indian Journal of Animal Production and Management, 2025)
A study was conducted in small holder production system to understand feeding practices of dairy farmers of Meerut district. 100 farmers having land holding up to 4 acres were selected randomly, 50 from rural and 50 from urban area of the district. A suitable interview schedule was developed for these farmers to record the observations. The study revealed major differences in rearing preferences of dairy farmers based on family and caste system in urban and rural area. Majority of dairy farmers had good experience in dairy farming with moderate income status. Significant differences were observed in feeding of roughages and concentrate to animals, formulation of concentrate and method of feeding concentrate to animals in the study area. Improved feeding techniques such as urea treatment, conservation of feed and fodder as hay and silage were less popular in both the areas of the study. The major limitations included problems related to infertility in animals, lesser knowledge of technology driven practices and unavailability of veterinary laboratory testing facilities in the area.
Keywords: Dairy farmers, Land holding, Production system, Income